2020
DOI: 10.15376/biores.15.4.7374-7389
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of lignin-TiO2 UV-shielding composite material by induced synthesis with nanofibrillated cellulose

Abstract: It is desirable to develop biodegradable ultraviolet (UV)-shielding materials from renewable resources, as the demand for sustainability is ever increasing. In this work, a novel lignin-TiO2 UV-shielding composite was synthesized successfully via a hydrothermal method induced by nanofibrillated cellulose (NFC). Comprehensive characterization showed that the lignin-TiO2@NFC composite induced by NFC had good nanoparticle size, shape, and thermal stability. The sunscreen performance of lignin-TiO2@NFC was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
(42 reference statements)
2
8
0
Order By: Relevance
“…Only in the composite PP-30 was it possible to observe a very weak absorption band located at 1604 cm −1 that could be associated to the interaction of the TiO 2 nanoparticles and lignin. A similar study was reported by Guo et al, who observed an absorption band located at 1631 cm −1 which was associated to the interaction of hydrogen bonds between lignin surface groups and TiO 2 nanoparticles [ 24 ]. In addition, in each FTIR spectrum of the composites, an absorption band centered at 560 cm −1 was located, which was attributed to the vibrations of Ti–O bonds that are characteristic of TiO 2 nanoparticles.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Only in the composite PP-30 was it possible to observe a very weak absorption band located at 1604 cm −1 that could be associated to the interaction of the TiO 2 nanoparticles and lignin. A similar study was reported by Guo et al, who observed an absorption band located at 1631 cm −1 which was associated to the interaction of hydrogen bonds between lignin surface groups and TiO 2 nanoparticles [ 24 ]. In addition, in each FTIR spectrum of the composites, an absorption band centered at 560 cm −1 was located, which was attributed to the vibrations of Ti–O bonds that are characteristic of TiO 2 nanoparticles.…”
Section: Resultssupporting
confidence: 77%
“…In addition, signals could be observed for 2θ values of 27.56, 36.28, 39.41, 41.46, 44.17, 54.53, 56.98, 62.96, 64.03, 69.09, and 69.98° corresponding to the Miller planes (110), (101), (200), (111), (210), (211), (220), (002), (310), (301), and (112) of the rutile crystalline phase (TiO 2 ) (JCDPS 21-1276), which confirms its incorporation into the polymeric matrix of the PP. However, it was not possible to determine the lignin phase due to the amorphous nature of the material, which lacks an ordered structure [ 24 ]. Furthermore, no increase in the intensity or width of the PP signals was observed, which suggests that the addition of TiO 2 had no effect on the crystalline structure of the polymeric matrix, as shown in the literature [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…7c). In addition, lignin can also be incorporated with TiO 2 in the formation of hydrogen bonds 89 and esterification reactions 90 to serve as the sunscreen ingredients. The resulting hybrid materials have demonstrated high UV light absorbance across the full UV region as well as the great UV scattering efficiency, indicating their good UV shielding ability.…”
Section: Design Of Polyphenolic Sunscreensmentioning
confidence: 99%
“…The existing methods for the synthesis of TiO 2 NPs utilizing lignin have used either high temperature (i.e., calcination at 300–900 °C) or harsh chemicals, which added extra cost to the synthesis and also caused environmental pollution. ,, ,,, Moreover, the synthesis of TiO 2 NPs was performed mostly via chemical routes, and lignin was added later into the chemically synthesized TiO 2 NPs. In a reported method, researchers have used modified industrial alkali lignin (AL) for the synthesis of the lignin/TiO 2 composite .…”
Section: Introductionmentioning
confidence: 99%
“…Further, the optimized lignin coating was doped with different concentrations (1−5% w/w to lignin) of commercial TiO 2 NPs, TiO 2 ALNCs, and TiO 2 KLNCs, separately. Notably, the lignin coating was doped with TiO 2 NCs because they are known for their UV-protective33,53,70 and antimicrobial behaviors 70. 74,81−83 The developed coatings showed good clarity (Figure 12a−d) and even distribution, as observed via a fluorescence microscope (Figure 12e−h).…”
mentioning
confidence: 99%